LC-MS/MS BASED DEREPLICATION OF ISOQUINOLINE-DERIVED ALKALOIDS FROM THE TRUNK BARK OF Unonopsis rufescens (Baill.) R.E.Fr. (Annonaceae) - Lucas Antônio F. de Almeida; Felipe Moura A. da Silva; Bruna Ribeiro de Lima; Aline Bastos B. de Sousa; Francinaldo A. da Silva Filho; Brenda R. C. Leocadio; Ana Paula A. Castro; Rebeca dos S. França; Hector H. F. Koolen; Afonso D. L. de Souza; Maria Lúcia B. Pinheiro (Química Nova)
Mass spectrometry-based approaches constitute the primary strategy for the dereplication of isoquinoline-derived alkaloids, which are widely distributed in various genera of the Annonaceae family. On the other hand, although many species from the Annonaceae family have been studied regarding their alkaloid content, others remain largely unexplored, such as U. rufescens. In order to dereplicate isoquinoline-derived alkaloids from the trunk bark of U. rufescens, a liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) analysis in positive ionization mode was conducted with its alkaloid fraction and the fragmentation data were subsequently interpreted manually. Based on the fragmentation pattern knowledge regarding isoquinoline-derived alkaloids, pallidine (1), along with the benzyltetrahydroisoquinolines coclaurine (2), N-methylcoclaurine (3), reticuline (5), norarmepavine (6), norjuziphine (7), and N-methylnorjuziphine (8); proaporphine stepharine (4); oxoaporphines liriodenine (10) and lysicamine (13); C-7 substituted aporphine norushinsunine (11); and the aporphines asimilobine (9), isopiline (12), nornuciferine (14), anonaine (15), and O-methylisopiline (16) were tentatively identified. In addition, a mixed fragmentation pathway was observed for isopiline (12), and a proposed fragmentation pathway for this compound was presented. Overall, this study expands the knowledge of U. rufescens, demonstrating the rich chemical diversity present in this species. Furthermore, it contributes to the research on the fragmentation patterns of isoquinoline-derived alkaloids.